Using a Genetically Encoded Sensor to Identify Inhibitors of Toxoplasma gondii Ca(2+) Signaling - Sidik, Saima M. (J Biol Chem, 2016)
The life cycles of apicomplexan parasites progress in accordance with fluxes in cytosolic Ca(2+). Such fluxes are necessary for events like motility and egress from host cells. We used genetically encoded Ca(2+) indicators (GCaMPs) to develop a cell-based phenotypic screen for compounds that modulate Ca(2+) signaling in the model apicomplexan Toxoplasma gondii. In doing so, we took advantage of the phosphodiesterase inhibitor zaprinast, which we show acts in part through cGMP-dependent protein kinase (protein kinase G; PKG) to raise levels of cytosolic Ca(2+). We define the pool of Ca(2+) regulated by PKG to be a neutral store distinct from the endoplasmic reticulum. Screening a library of 823 ATP mimetics, we identify both inhibitors and enhancers of Ca(2+) signaling. Two such compounds constitute novel PKG inhibitors and prevent zaprinast from increasing cytosolic Ca(2+). The enhancers identified are capable of releasing intracellular Ca(2+) stores independently of zaprinast or PKG. One of these enhancers blocks parasite egress and invasion and shows strong antiparasitic activity against T. gondii. The same compound inhibits invasion of the most lethal malaria parasite, Plasmodium falciparum. Inhibition of Ca(2+)-related phenotypes in these two apicomplexan parasites suggests that depletion of intracellular Ca(2+) stores by the enhancer may be an effective antiparasitic strategy. These results establish a powerful new strategy for identifying compounds that modulate the essential parasite signaling pathways regulated by Ca(2+), underscoring the importance of these pathways and the therapeutic potential of their inhibition.